2021
DOI: 10.1038/s41598-021-03821-8
|View full text |Cite
|
Sign up to set email alerts
|

Coupled changes in western South Atlantic carbon sequestration and particle reactive element cycling during millennial-scale Holocene climate variability

Abstract: AbstractContinental shelves have the potential to remove atmospheric carbon dioxide via the biological pump, burying it in seafloor sediments. The efficiency of marine carbon sequestration changes rapidly due to variations in biological productivity, organic carbon oxidation, and burial rate. Here we present a high temporal resolution record of marine carbon sequestration changes from a western South Atlantic shelf site sensitive to Brazil Current-driven upwelling. The comparison of biological records to rare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 62 publications
(123 reference statements)
0
2
0
Order By: Relevance
“…We also applied the BFAR index, calculated here as the total number of benthic foraminifera multiplied by the sediment accumulation rate as it has been shown to be a reliable proxy for the organic carbon flux to the seafloor in the Brazilian margin (Dias et al, 2021). The BFAR index represents the increments of primary productivity export to the seafloor, in which the increases on benthic biomass are associated to the increasing food availability to the benthic community (Herguera and Berger, 1991;Guichard et al, 1997;Jorissen et al, 2007).…”
Section: Productivity Proxiesmentioning
confidence: 99%
See 1 more Smart Citation
“…We also applied the BFAR index, calculated here as the total number of benthic foraminifera multiplied by the sediment accumulation rate as it has been shown to be a reliable proxy for the organic carbon flux to the seafloor in the Brazilian margin (Dias et al, 2021). The BFAR index represents the increments of primary productivity export to the seafloor, in which the increases on benthic biomass are associated to the increasing food availability to the benthic community (Herguera and Berger, 1991;Guichard et al, 1997;Jorissen et al, 2007).…”
Section: Productivity Proxiesmentioning
confidence: 99%
“…This limitation arises from the lack of calibration across various productivity settings, among other factors (for an in-depth discussion, please refer to Jorissen et al, 2007). However, Dias et al (2021) demonstrated that the BFAR can indicate variations in the Cabo Frio Upwelling System, located in the SEBCM, where higher BFAR values correspond to increased export of fresh marine organic carbon.…”
Section: Organic Matter Export and Seafloor Dynamicsmentioning
confidence: 99%